El modelo mental compartido de los recursos humanos desde la perspectiva de la teoría feminista de la organización (The human resources shared mental model from the perspective of the feminist theory of the organization) - Mendoza Gómez, Joel (Facultad de Contaduría Pública y Administración U.A.N.L., 2012)
Abstract. The object of this article is the integration of feminist and team shared mental model theories. Through this integration, we question the implementation of some techniques oriented to reinforce the effectiveness of the human resources of the organization, and why they are not as effective as they were expected to be. The answer to this question is conceptually developed through the revision of the elements of both theories. By this revision, a feminine shared mental model is identified and some propositions are derived about the tasks and processes of the group and the organization; Thus they are oriented to achieve a better performance of the human resources that form part of the group and the organization.